USAHA HITRO MART KANDANGAN DITINJAU DARI ASPEK PEMASARAN DAN TEKNIS - Dita Indah Lestari; Nurul Fitria Hayati; Eka Wilinda; Muhammad Firliandi Noor Salim (Program Studi Ekonomi Syariah, 2024)
The purpose of this study is to examine the Hitro Mart Kandangan business's viability from a technical and marketing standpoint. Hitro Mart is a minimarket that prioritizes accessibility and convenience in order to meet the community's everyday requirements. Through literature studies, interviews, and direct observation, this study employs a qualitative descriptive methodology. The results of the study demonstrate how successful the marketing plan is, bolstered by competitive pricing, focused market segmentation, and social and local media promotion. Technically speaking, the store layout is made to improve efficiency and convenience by carefully positioning the cashier area and frequently grouping items. Dependency on specific suppliers is one of the many challenges that must be taken into account. All things considered, Hitro Mart has a lot of room to grow by improving both areas.